1996
DOI: 10.1128/aem.62.3.791-797.1996
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the enterohemorrhagic Escherichia coli O157 DNA region containing lambdoid phage gene p and Shiga-like toxin structural genes

Abstract: In this study, we determined the nucleotide sequence of the p gene contained within a 5-kb EcoRI restriction fragment cloned from Shiga-like toxin II (SLT-II)-converting phage 933W of Escherichia coli O157:H7 strain EDL933. The p gene was 702 bp long and had 95.3% sequence similarity to the p gene of phage. Multiple hybridization patterns were obtained when genomic DNA fragments were hybridized with both p and slt-I, slt-II, or slt-IIc sequences. All O157 isolates also possessed an analog of gene p which was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The plaques of Stx2⌽-II developed in C600 were significantly smaller than those of Stx2⌽-I, for which the morphology of plaques resembled that of 933W. Although the full length of the Stx2⌽-I genome was similar to that of 933W (7,34,45,49), it was approximately 3 kb smaller than that of Stx2⌽-II (Fig. 2).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The plaques of Stx2⌽-II developed in C600 were significantly smaller than those of Stx2⌽-I, for which the morphology of plaques resembled that of 933W. Although the full length of the Stx2⌽-I genome was similar to that of 933W (7,34,45,49), it was approximately 3 kb smaller than that of Stx2⌽-II (Fig. 2).…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we sequenced the two stx2 genes in Stx2⌽-I and Stx2⌽-II and found that the two stx2 sequences were identical to each other and that they were also identical to the stx2 gene from 933W (11,21,22,54). The open reading frames containing the stx2 gene of Stx2⌽-I and Stx2⌽-II were located downstream of p gene of phage , as is the case for the stx2 gene in 933W (7,45).…”
Section: Isolation Of Stx2-converting Phages From Stec Strainsmentioning
confidence: 88%
See 1 more Smart Citation
“…Significant genomic divergence among Stx1-encoding phages isolated from different E. coli serotypes has been dem-onstrated by analysis of phage genome lengths and restriction fragment length polymorphisms (RFLP) (25). Recent studies have revealed some variation within O157-derived Stx2-encoding phages (6,22). In the present study, to assess the level of variation among Stx2-encoding phages derived from multiple STEC serotypes and its possible relevance to toxin regulation, we produced isogenic lysogens of seven different Stx2-encoding phages.…”
mentioning
confidence: 99%
“…Long-PCR restriction fragment length polymorphism (RFLP) was employed to target sequences between the p gene (analogous to the k phage replication promoter) and the VT2A subunit, because VT2 sequences can be encoded by lamboid phages. A 45°C annealing step and primers DK1 and GK7 were used (Datz et al 1996). The reaction mix was modified to contain ca 100 ng genomic DNA, 200 lM M of each deoxynucleoside triphosphate, 200 nM M of each primer, 5 ll of 10X PCR buffer, and 2AE6 U of expand high fidelity polymerase (Expand TM ; Roche Diagnostics, Lewes, UK), in a final volume of 50 ll.…”
Section: Further Subtypingmentioning
confidence: 99%